Relationship between anthropometric measures and the risk of incident Metabolic dysfunction-associated steatotic liver disease: a longitudinal study - Takahiro Ichikawa; Yoshitaka Hashimoto; Takuro Okamura; Akihiro Obora; Takao Kojima; Hiroshi Okada; Masahide Hamaguchi; Michiaki Fukui (BMC Gastroenterology)
Abstract Background Waist circumference (WC) and body mass index (BMI) are considered useful for the diagnosis of metabolic dysfunction-associated steatotic liver disease (MASLD). This study aimed to investigate the association between the body roundness index (BRI) and a body shape index (ABSI) with incident MASLD, in comparison to WC and BMI. Methods Retrospective cohort data from a Japanese health check-up program were analyzed. Logistic regression model was used to evaluate the associations between anthropometric measure quartiles and MASLD, and receiver operating characteristic (ROC) analysis was performed to evaluate the associations between anthropometric measures and incident MASLD, stratified by sex. Results A total of 10,561 males and 7,187 females were included, of whom 3,182 males and 914 females developed MASLD. Multivariate analysis revealed that higher WC, BMI, and BRI were associated with incident MASLD in both sexes, whereas higher ABSI was significantly associated with incident MASLD only in females. Among males, the area under the ROC curve (AUC) of BMI was higher than that of WC, BRI, and ABSI. Conversely, among females, the AUC of BMI was higher than that of ABSI, whereas it was comparable to that of WC or BRI. The AUC and the optimal cut-off values of BMI for predicting incident MASLD were 0.77 and 23.9 kg/m2 in males, and 0.86 and 22.2 kg/m2 in females. The optimal cut-off values of WC were 82.0 cm for males and 76.3 cm for females, respectively. Conclusions We demonstrated the strongest association between BMI and incident MASLD compared to other measures, particularly in males, while also showing a strong association in females. Additionally, specific WC criteria for Asians to improve MASLD diagnosis are needed.